АРPLICATION OF FISH-METHOD IN IDENTIFICATION OF CRYPTIC MOSAICISM INVOLVING SEX CHROMOSOMES IN COUPLES WITH REPRODUCTIVE FAILURE - Denysenko, S. V. (Medical Informatics and Engineering, 2012)
The application of FISH-method on interphase cells with centromeric probes for chromosomes X and Y is described as used together with the traditional cytogenetic methods for the screening minor sex aneuploid cell lines among the couples with reproductive problems.